Photoacidity and Photodegradation within Polyelectrolyte/TiO2Suspensions and Coatings - Mueller, Martin; Vsivcev, Dmitrij; Urban, Birgit; Wendler, Felix; Schacher, Felix H.; Fery, Andreas (ACS Applied Polymer Materials, 2022)
Photocatalytic coatings represent dynamic light switchable interfaces and offer applications in industrial and even personal waste water treatment concerning pollutant removal. In this framework, nanoparticular suspensions and scalable coatings composed of TiO2and weak polyelectrolytes (PE) were generated and studied concerning photoacidity and photodegradation applying UV light at a wavelength close to the band gap of TiO2. The TiO2modifications anatase and rutile and anionic poly(acrylic acid) (PAA), cationic poly(allylamine) (PAH), and ampholytic poly(dehydroalanine-graft-phosphonylacrylamide) (PDHAG) were utilized at germanium model substrates. Colloid, interfacial, and photocatalytic properties were investigated by potentiometry, dynamic light scattering (DLS), Fourier transform infrared (FTIR) spectroscopy, and scanning force microscopy (SFM). Upon UV illumination at 365 nm, all PE/anatase suspensions showed a significant pH decrease from pH = 6.00 down to pH = 5.27 and, partly, chemical changes within the PE fraction, while PE/rutile suspensions did not show such a pH drop. In comparison to the suspensions, PE/anatase coatings revealed less photoacidic properties but significant photocatalytic degradation of the bound PE, while this effect was absent in the case of PE/rutile samples. In application studies, acetate or anti-inflammatory drug flufenamic acid loaded into PE/anatase coatings could be significantly degraded upon UV illumination.
CRIS-Team Scopus Importer:2023-03-20
Keywords: anatase; FTIR spectroscopy; photoacidity; photocatalysis; photodegradation; poly(acrylic acid); poly(allylamine); poly(dehydroalanine- graft-phosphonylacrylamide); rutile; titanium dioxide